Laporan Kasus: Tatalaksana Pneumonia Komunitas di Rumah Sakit Toto Kabila - Papeo, Dizky Ramadani Putri; Putra, Andi El Jalaludin; Gubali, Jihan AR.; Gilalom, Amanda Septiyani; Abd. Latif, Novia Nur Agiska; Idrus Mohamad, Marsela; Ngani, Altaufik (Lontara Journal of Health Science and Technology, 2026)
Pneumonia is an acute respiratory infection affecting the terminal bronchioles and alveoli, commonly caused by bacteria, viruses, or fungi, and remains a leading cause of morbidity and mortality, particularly in extreme age groups. This study aims to describe the clinical presentation, risk factors, and evaluate diagnostic and therapeutic approaches in a patient with community-acquired pneumonia at Toto Kabila General Hospital. A case study was conducted on a 77-year-old male patient presenting with a three-day fever, two-month chronic cough, and epigastric pain. Diagnosis was established through history taking, physical examination, chest X-ray showing bilateral patchy opacities and aortic dilatation, and laboratory tests including hematology, clinical chemistry, and Widal serological test. Treatment included intravenous followed by oral levofloxacin, fluid infusion, antipyretics, N-acetylcysteine and ambroxol, vitamins, and albumin to correct hypoalbuminemia. Data were analyzed descriptively to assess the consistency between clinical findings, diagnosis, and therapeutic response. Laboratory results revealed leukocytosis (12.38×10³/µL), mild hypoalbuminemia (2.4 g/dL), and a positive Widal titer of 1/320, supporting a diagnosis of bilateral pneumonia with secondary typhoid fever. After seven days of treatment, the patient showed improvements in body temperature, respiratory function, and sputum clearance, along with better hemodynamic stability. A multimodal pharmacological and non-pharmacological approach was effective in improving the clinical condition of an elderly pneumonia patient.